STUDI TENTANG PENGARUH BUDAYA ORGANISASI DAN DESAIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SUCOFINDO CABANG JAMBI - Prayoga , Aryo (Jurnal Development, 2025)
This study aims to analyze the influence of organizational culture and job design on employee job satisfaction at PT. Sucofindo Jambi Branch. Organizational culture and job design are two key factors believed to play a significant role in creating optimal job satisfaction within the testing, inspection, and certification (TIC) service industry. A strong organizational culture particularly one based on the AKHLAK values (Amanah/Trustworthy, Kompeten/Competent, Harmonis/Harmonious, Loyal/Loyal, Adaptif/Adaptive, and Kolaboratif/Collaborative) is expected to enhance employees’ sense of belonging, loyalty, and psychological well-being. Meanwhile, an effective job design covering task variety, role clarity, autonomy, and feedback can foster intrinsic motivation and satisfaction with one’s work. This study employed a quantitative approach with descriptive methods and multiple linear regression analysis. The research sample consisted of 57 employees of PT. Sucofindo Jambi Branch. The results indicate that both organizational culture and job design have a positive and significant effect on employee job satisfaction. The beta coefficient values show that organizational culture (β = 0.635) has a more dominant influence than job design (β = 0.223), while the coefficient of determination (R² = 0.673) indicates that both variables together explain 67.3% of the variance in job satisfaction. These findings suggest that the internalization of a strong organizational culture and the implementation of meaningful job design can simultaneously enhance employee satisfaction, commitment, and productivity. Therefore, strengthening the AKHLAK work culture and optimizing adaptive job design in response to technological developments are crucial strategies for PT. Sucofindo Jambi Branch to sustainably improve human resource performance and well-being.